Porous carbon framework material, lithium-carbon composite material and preparation method and application thereof

By using a porous carbon skeleton material with a core-shell structure in the lithium carbon composite material, the deposition path of metal lithium is regulated, and the problem of metal lithium being difficult to deposit inside the carbon skeleton is solved, achieving high specific capacity and good cycle stability.

CN119627106APending Publication Date: 2025-03-14CHINA ENERGY LITHIUM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311181082.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the existing lithium-carbon composite materials, metal lithium is difficult to effectively deposit inside the carbon skeleton, resulting in poor formation and cycle stability of lithium dendrites.

Method used

Through the porous carbon skeleton material with a core-shell structure, the inner core is composed of lithium-philic carbon material particles, and the outer shell is constructed of lithium-repellent carbon material to form a gradient-distributed pore structure, regulating the deposition path of metal lithium to ensure uniform deposition inside the carbon skeleton.

Benefits of technology

The specific capacity and cycle stability of lithium-carbon composite materials have been significantly improved, and the volume expansion problem during the charging and discharging of metal lithium is alleviated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627106A_ABST
    Figure CN119627106A_ABST
Patent Text Reader

Abstract

The invention provides a porous carbon framework material, a lithium-carbon composite material and a preparation method and application thereof. The porous carbon framework material comprises an inner core formed by lithium-loving carbon material particles, a lithium-phobic porous shell is arranged on the surface of the inner core, and the lithium-carbon composite material comprises the carbon framework material and metal lithium filled in any position of the inner surface, pores and the outer surface of a carbon framework. Through ingenious arrangement of the lithium-loving-lithium-phobic core-shell structure, lithium ions penetrate through the lithium-phobic shell to deposit towards the inner core, deposition of metal lithium is effectively regulated and controlled, lithium dendrites are inhibited, and meanwhile the problem of volume expansion in the metal lithium charging and discharging process is relieved. The lithium metal composite material is prepared by adopting a liquid phase method, the process is simple, the content of each component can be regulated and controlled, and industrial production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and in particular relates to a lithium-carbon composite material and a preparation method and application thereof. Background Art

[0002] As one of the mainstream commercial batteries, lithium-ion batteries are widely used in electronic devices, new energy vehicles, and energy storage power stations. However, they cannot meet the growing demand for high energy density. Metallic lithium has a very high theoretical specific capacity (3860mAh / g), a relatively low potential (-0.304V vs. SHE), and a very small density (0.53g / cm 3 ), known as one of the negative electrode materials for the next generation of lithium-ion batteries, but metallic lithium has problems such as the generation of lithium dendrites or dead lithium and volume expansion during use.

[0003] In order to solve the above-mentioned problems, researchers have conducted research from the aspects of metal lithium negative electrode modification and electrolyte modification. Among them, in terms of metal lithium negative electrode modification, introducing carbon material as a skeleton is the first choice. CN 105374991A discloses a metal lithium-carbon nanotube microsphere composite material, which has a micron spherical structure, including carbon nanotube microspheres as porous carbon material carriers and metal lithium formed in the pores of the carbon nanotube microspheres. The composite material can inhibit lithium dendrites to a certain extent, but the affinity between metal lithium and carbon nanotube microspheres is poor and the specific capacity is low.

[0004] CN 109309201 A discloses a porous carbon skeleton-nanoparticle composite material, a metal lithium composite thereof, a preparation method and application thereof. The porous carbon skeleton-nanoparticle composite material comprises lithium-reactive metal or its oxide nanoparticles distributed in the pores and on the surface of the porous carbon skeleton. The porous carbon skeleton-nanoparticle composite material can reduce the nucleation energy when metal lithium is bound to the porous carbon skeleton or improve the affinity between lithium and skeleton carbon, but the lithium-reactive metal or its oxide nanoparticles are distributed on the entire porous carbon skeleton, and the metal lithium will preferentially deposit on the outer surface of the porous carbon skeleton and is difficult to enter the pores of the carbon skeleton. Therefore, it is impossible to effectively inhibit lithium dendrites and improve cycle stability.

[0005] Based on this, how to develop a high specific capacity lithium-carbon composite material that can avoid the preferential deposition of metallic lithium on the outer surface of the carbon skeleton, make the metallic lithium preferentially deposit inside the carbon skeleton, and at the same time alleviate the volume expansion problem of metallic lithium during the charging and discharging process has become an urgent problem that needs to be solved. Summary of the invention

[0006] The present invention aims to effectively solve the above technical problems. The inventors found that by coating the surface of a granular lithium-philic carbon material with a lithium-phobic carbon material to form a core-shell structured porous carbon skeleton material, the pore size of the porous carbon skeleton material is distributed in a gradient, which is beneficial to the transmission of lithium ions while alleviating the problem of volume expansion during the charging and discharging of metallic lithium. It can also effectively regulate the preferential deposition of metallic lithium on the surface of the granular lithium-philic carbon material, inhibit lithium dendrites, and significantly improve the specific capacity and cycle stability of the lithium-carbon composite material containing the porous carbon skeleton material.

[0007] In the first aspect, the present invention provides a porous carbon skeleton material, which is a granular material having a core-shell structure consisting of a core and a porous shell, wherein the core is formed by one or more lithium-philic carbon material particles, and the lithium-philic carbon material particles include a granular carbon material and a lithium-philic material deposited on the surface of the granular carbon material; the porous shell is arranged on the surface of the core and is formed by interweaving lithium-phobic carbon materials; the shape of the lithium-phobic carbon material includes any one of linear, tubular or flaky shapes or a combination of at least two of them.

[0008] In the present invention, in the porous carbon skeleton of the core-shell structure, the kernel is a sphere or spheroid with a smaller pore size formed or aggregated by lithium-philic carbon material particles, and the kernel has good affinity with metallic lithium, and can regulate metallic lithium to preferentially deposit inside the carbon skeleton, so that metallic lithium is filled from the kernel to the shell, and the specific capacity of the lithium-carbon composite material is improved while effectively suppressing lithium dendrites; the shell is a shell layer with a larger pore size constructed by a linear, tubular or sheet-like lithium-phobic carbon material, and the shell is not affinity to metallic lithium compared to the kernel, guiding lithium ions to be transmitted inwardly and then deposited, while supporting and restraining the kernel, alleviating the volume expansion problem during the charge and discharge process of metallic lithium. The present invention is cleverly arranged by the porous carbon skeleton of the lithium-philic-phobic lithium core-shell structure, and realizes simultaneous regulation of electric field and concentration field, so that the lithium-porous carbon skeleton composite material has good cycle stability and high specific capacity.

[0009] Optionally, the average particle size of the granular carbon material is 10nm-50μm, for example, it can be 10nm, 15nm, 30nm, 50nm, 100nm, 200nm, 500nm, 1000nm, 1.5μm, 3μm, 5μm, 10μm, 20μm, 30μm, 40μm or 50μm, etc., including but not limited to the listed point values, as long as they are within the above range, they all belong to the protection scope of the present invention, preferably 30nm-20μm, and more preferably 50nm-10μm. The granular carbon material within the range of the average particle size is easy to shape and can construct a stable core. The average particle size of the granular carbon material is tested using a laser diffraction particle size analyzer.

[0010] Optionally, the granular carbon material includes any one or a combination of at least two of Ketjen black, conductive graphite, acetylene black, Super P, LITX, natural graphite, artificial graphite, fluorinated graphite or activated carbon, preferably any one or a combination of at least two of Ketjen black, acetylene black, Super P or fluorinated graphite. The granular carbon material has a large specific surface area and can carry a richer lithium-philic material; it has good electrical conductivity and a relatively uniform current density on the core, which is conducive to the uniform deposition of metallic lithium.

[0011] Optionally, the lithium-philic material includes any one of silver, gold, tin, silicon, boron, gallium, aluminum, indium, magnesium or antimony, or a combination of at least two of them.

[0012] Optionally, the molar ratio of the lithium-philic material to the granular carbon material in the lithium-philic carbon material particles is 1:(0.5-100), for example, it can be 1:0.5, 1:1, 1:3, 1:5, 1:10, 1:12.5, 1:15, 1:20, 1:30, 1:40, 1:45, 1:47.5, 1:50, 1:70, 1:90 or 1:100, etc. The molar ratio enables the lithium-carbon composite material to take into account both specific capacity and cycle stability, preferably 1:(10-50).

[0013] Optionally, the average pore size of the core is 1-10 nm, for example, 1 nm, 1.5 nm, 2 nm, 5 nm, 7 nm, 9 nm or 10 nm, including but not limited to the listed point values, as long as they are within the above range, they belong to the protection scope of the present invention. The average pore size is measured by gas adsorption method, and the measuring gas is nitrogen.

[0014] Optionally, the lithium-phobic carbon material includes a micro-nano carbon material and a lithium-phobic layer on the surface of the micro-nano carbon material, wherein the micro-nano carbon material includes any one of single-walled carbon nanotubes, multi-walled carbon nanotubes, double-walled carbon nanotubes, carbon nanofibers or graphene, or a combination of at least two thereof; the lithium-phobic layer includes a lithium-phobic element, and the lithium-phobic element is any one of copper, nickel, iron, chromium, manganese, cobalt, vanadium or titanium, or a combination of at least two thereof. Examples of lithium-phobic carbon materials include, but are not limited to, copper-plated single-walled carbon nanotubes, nickel-plated multi-walled carbon nanotubes, copper-plated multi-walled carbon nanotubes, chromium-plated carbon nanofibers, cobalt-plated graphene or copper-plated carbon fibers, etc.

[0015] Optionally, based on the mass of the lithium-phobic carbon material as 100%, the mass fraction of the lithium-phobic layer is less than 60%, for example, it can be 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10% or 5%, etc., including but not limited to the listed point values, as long as they are within the above protection scope, they belong to the protection scope of the present invention, preferably 30-50%.

[0016] Optionally, the molar ratio of the lithium-philic material in the inner core to the lithium-phobic element in the lithium-phobic layer is (1-10):1, that is, the molar ratio of the lithium-philic element and the lithium-phobic element in the porous carbon skeleton can be, for example, 1:1, 1.5:1, 2:1, 3:1, 4:1, 4.5:1, 5:1, 7:1, 9:1 or 10:1, etc., including but not limited to the listed point values, as long as they are within the above protection range, they all belong to the protection scope of the present invention. The molar ratio is less than 1:1, the lithium-philic material is too little, and the effect of regulating the deposition of metallic lithium is limited; the molar ratio is greater than 10:1, the lithium-phobic element in the lithium-phobic layer is too little, and the transmission of lithium ions cannot be effectively regulated, preferably (1.5-5):1.

[0017] Optionally, the average particle size of the porous carbon skeleton of the core-shell structure is 1-100 μm, for example, it can be 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm, 45 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, including but not limited to the listed point values, as long as they are within the above protection range, they belong to the protection scope of the present invention, preferably 5-50 μm. The average particle size is tested using a laser diffraction particle size analyzer.

[0018] Optionally, the mass ratio of the inner core to the porous outer shell in the porous carbon skeleton of the core-shell structure is (1-100):1, for example, it can be 1:1, 3:1, 5:1, 10:1, 12:1, 15:1, 20:1, 30:1, 40:1, 45:1, 50:1, 70:1, 90:1 or 100:1, etc., including but not limited to the listed point values. As long as they are within the above protection scope, they belong to the protection scope of the present invention. If the mass ratio is too small, the mass of the inner core is small, and the regulation of the deposition of metallic lithium is limited; if the mass ratio is too large, the mass of the outer shell is small, and the transport and guidance effect of lithium ions is not obvious, preferably (10-50):1.

[0019] In a second aspect, the present invention provides a lithium-carbon composite material, which includes the above-mentioned porous carbon skeleton material and metallic lithium filled in the pores of the porous carbon skeleton material and / or distributed on the inner and outer surfaces of the porous carbon skeleton material.

[0020] Optionally, taking the total mass of the lithium-carbon composite material as 100%, the mass fraction of metallic lithium in the lithium-carbon composite material is greater than 50%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%, etc., including but not limited to the listed point values, as long as they are within the above protection scope, they belong to the protection scope of the present invention, preferably 60-90%.

[0021] In a third aspect, the present invention provides a method for preparing the lithium-carbon composite material described in the second aspect, the method comprising the following steps:

[0022] (1) mixing a granular carbon material, a lithium-philic element halide and an organic solvent to obtain a mixed system, adding a strong reducing agent (e.g., a low concentration of metallic lithium solution) to the mixed system and reacting the system under shaking or stirring, and then optionally drying (e.g., spray drying) to obtain a lithium-philic carbon material core;

[0023] The organic solvent includes any one or a combination of at least two of acetonitrile, N-methylpyrrolidone, liquid ether, liquid ester, liquid alkane or liquid aromatic hydrocarbon;

[0024] The metallic lithium solution comprises a liquid ammonia solution of metallic lithium and / or an organic amine solution of metallic lithium, and the concentration is lower than 5 mol / L;

[0025] (2) mixing the lithium-philic carbon material core, the lithium-phobic carbon material and the organic solvent in step (1), and spray granulating the mixture to obtain a porous carbon skeleton material with a core-shell structure;

[0026] The shape of the lithium-phobic carbon material includes any one of linear, tubular or sheet-like shapes or a combination of at least two of them;

[0027] The organic solvent may be the same as the organic solvent in step (1) or different. For example, ethanol, ethylene glycol, acetone or tetrahydrofuran may be used alone or in combination, as long as the organic solvent can form a porous carbon skeleton with a core-shell structure.

[0028] (3) immersing the carbon skeleton in step (2) in a high concentration of metallic lithium solution, and then drying, or using evaporation and / or molten lithium perfusion methods to allow metallic lithium to exist in the pores and / or on the inner and outer surfaces of the porous carbon skeleton material, to obtain a lithium-carbon composite material; the method for composite with metallic lithium is preferably a method of molten lithium perfusion and / or impregnation;

[0029] The metallic lithium solution includes a liquid ammonia solution of metallic lithium and / or an organic amine solution of metallic lithium, and the concentration thereof is higher than 6 mol / L.

[0030] In the present invention, the concentration of the metallic lithium solution in step (1) can be 5 mol / L, 4.5 mol / L, 4 mol / L, 3.5 mol / L, 3 mol / L, 2.5 mol / L, 2 mol / L, 1.5 mol / L, 1 mol / L, 0.5 mol / L, 0.3 mol / L, 0.1 mol / L or 0.05 mol / L, including but not limited to the listed point values. As long as they are within the above protection range, they belong to the protection scope of the present invention.

[0031] In the present invention, the concentration of the metallic lithium solution in step (3) can be 6 mol / L, 6.5 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 9.5 mol / L, 10 mol / L or 15 mol / L, including but not limited to the listed point values. As long as they are within the above protection range, they belong to the protection scope of the present invention.

[0032] In the present invention, the strong reducing property of metallic lithium is utilized. In step (1), a low concentration of metallic lithium solution is used to react with a lithium-philic element halide to undergo an oxidation-reduction reaction, thereby obtaining lithium-philic carbon material particles in which the lithium-philic material is in situ grown on the surface of a granular carbon material. In step (2), spray granulation is performed to construct a porous carbon skeleton with a core-shell structure having a granular lithium-philic carbon material as a core and a lithium-phobic carbon material as an outer shell. Due to the difference in properties such as shape between the core and the outer shell, a porous carbon skeleton with a small core pore size and a large outer shell pore size is formed, that is, the pore size in the porous carbon skeleton is distributed in a gradient from the inside to the outside. In step (3), a liquid phase method, evaporation or molten lithium infusion method is used to compound metallic lithium with a porous carbon skeleton, and metallic lithium is preferentially deposited on the core, and then filled into any position of the inner surface, pores or outer surface of the porous carbon skeleton to obtain a lithium-carbon composite material. The method is simple in process, can regulate the content of each component, and is easy to industrialize.

[0033] In the present invention, the granular lithium-philic carbon material and the lithium-phobic carbon material can be purchased, such as existing products produced by Beijing Dekedaojin Technology Co., Ltd., or materials obtained by a method similar to step (1). For example, the lithium-phobic carbon material can be prepared by the following method:

[0034] A carbon material in at least one shape of line, tube or sheet, a lithium-phobic element halide and an organic solvent are mixed to obtain a mixed system, a strong reducing agent (for example, a low concentration of metallic lithium solution) is added to the mixed system and reacted under shaking or stirring to obtain a lithium-phobic carbon material.

[0035] Specifically, graphene, titanium tetrachloride and p-xylene are uniformly mixed, and then a 0.5 mol / L metallic lithium methylamine solution is added, and ultrasonic vibration is performed to react to obtain titanium-coated graphene, that is, lithium-phobic carbon material.

[0036] Optionally, the molar ratio of the metallic lithium in the metallic lithium solution and the lithiophilic element in the lithiophilic element halide in step (1) is (1-5):1, for example, it can be 1:1, 1.5:1, 2:1, 3:1, 4:1, 4.5:1 or 5:1, including but not limited to the listed point values, as long as they are within the above protection scope, they belong to the protection scope of the present invention.

[0037] Optionally, the organic solvent in step (1) includes any one or a combination of at least two of n-pentane, n-hexane, cyclohexane, N-methylpyrrolidone, benzene, p-xylene, carbon tetrachloride, tetrahydrofuran, liquid paraffin or 1,2-dichloroethane, preferably any one or a combination of at least two of N-methylpyrrolidone, p-xylene, tetrahydrofuran or benzene.

[0038] Optionally, the concentration of the metallic lithium solution in step (1) is (0.1-4) mol / L, preferably (2-3.5) mol / L.

[0039] Optionally, the organic solvent in step (2) includes any one of N-methylpyrrolidone, ethanol, ethylene glycol, acetone, tetrahydrofuran, n-hexane, p-xylene, heptane or ethylene glycol dimethyl ether, or a combination of at least two thereof.

[0040] Optionally, the concentration of the metallic lithium solution in step (3) is (6-10) mol / L.

[0041] In a fourth aspect, the present invention provides a metal lithium composite negative electrode, wherein the metal lithium negative electrode comprises the lithium-carbon composite material described in the third aspect.

[0042] In the present invention, in the metal lithium composite negative electrode, the three-dimensional skeleton of the granular lithium-philic carbon material and the lithium-phobic carbon material is evenly distributed, which effectively regulates the electric field and ion field of the negative electrode, realizes the uniform deposition of metal lithium and alleviates the volume expansion of metal lithium; the composite negative electrode has excellent cycle stability.

[0043] In a fifth aspect, the present invention provides a lithium battery, the lithium battery comprising the metal lithium composite negative electrode as described above. The positive electrode of the lithium battery includes but is not limited to at least one of lithium nickel cobalt manganese oxide, nickel cobalt aluminum manganese oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate, elemental sulfur, polyacrylonitrile sulfide or oxygen. The positive and negative electrodes of the battery are highly compatible and have excellent electrochemical properties.

[0044] The present invention has at least one of the following beneficial technical effects:

[0045] 1. In the porous carbon skeleton material provided by the present invention, the inner core composed of the lithium-philic carbon material particles has good affinity with metallic lithium, and the metallic lithium is regulated to preferentially deposit inside the carbon skeleton, and the metallic lithium is filled from the inner core to the outer shell; the outer shell is composed of the lithium-phobic carbon material, and the metallic lithium is guided to deposit into the inner core. The inner core and the outer shell are designed by the lithium-philic-lithium-phobic structure, and the electric field and the concentration field are regulated at the same time. The lithium-carbon composite material containing the porous carbon skeleton material has good cycle stability and high specific capacity;

[0046] 2. In the porous carbon skeleton material provided by the present invention, the lithium-philic carbon material particles form a porous inner core with a smaller pore size, and the linear, tubular or sheet-like lithium-phobic carbon material forms a porous outer shell with a larger pore size. The two together construct a porous skeleton with a pore size gradient, which is beneficial to the transmission of lithium ions;

[0047] 3. The present invention improves the cycle performance of the lithium-carbon composite material by further optimizing the molar ratio of the lithium-philic material to the granular carbon material, the molar ratio of the lithium-philic element to the lithium-phobic element and other parameters in the porous carbon skeleton material;

[0048] 4. The method of the present invention is simple and easy to implement. A porous carbon skeleton material with a pore size gradient distribution and a lithium-philic-lithium-phobic structure is spontaneously formed through the preparation method. The metallic lithium content in the lithium-carbon composite material prepared therefrom can be controlled, and it is easy to industrialize and produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 A cross-sectional schematic diagram of a porous carbon skeleton material provided by the present invention;

[0050] Figure 2 is a SEM image of the lithium-carbon composite material prepared in Example 2;

[0051] Figure 3 The composite materials in Example 2 and Comparative Example 1 at 1 mA / cm 2 and 1mAh / cm 2 Test curve under conditions;

[0052] Figure 4 The composite materials in Example 2 and Comparative Example 2 are 2 and 1mAh / cm 2 Test curve under conditions;

[0053] Figure 5 The composite materials in Example 2 and Comparative Example 3 are 2 and 1mAh / cm 2 Test curve under conditions;

[0054] Figure 6 The composite materials in Example 2 and Comparative Example 4 are 2 and 1mAh / cm 2 Test curve under conditions;

[0055] Figure 7 The composite materials in Example 2 and Comparative Examples 5-7 are at 1 mA / cm 2 and 1mAh / cm 2 Test curve under conditions.

[0056] 1-porous carbon skeleton material, 2-core, 21-granular carbon material, 22-lithium-philic material, 3-porous shell. DETAILED DESCRIPTION

[0057] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] The porous carbon skeleton material provided by the present invention is illustrated by way of example. Figure 1 A cross-sectional schematic diagram of a porous skeleton carbon material provided by the present invention; the porous carbon skeleton material 1 is a granular material having a core-shell structure consisting of a core 2 and a porous shell 3, wherein the core 2 is formed by lithium-philic carbon material particles, and the lithium-philic carbon material particles include a granular carbon material 21 and a lithium-philic material 22 deposited on the surface of the granular carbon material; the porous shell 3 is arranged on the surface of the core and is formed by interweaving lithium-phobic carbon materials.

[0059] Example 1

[0060] This embodiment provides a lithium-carbon composite material, and the preparation method of the lithium-carbon composite material comprises the following steps:

[0061] (1) 19 g of silver fluoride, 1.8 g of acetylene black (Henan Ruibo Chemical Co., Ltd., average particle size 30 nm), 1000 mL of acetonitrile and n-hexane were mixed evenly, and then 0.5 mol / L of metallic lithium in liquid ammonia solution was added, shaken to react completely, and then spray dried to obtain a granular lithium-philic carbon material core;

[0062] (2) the granular lithium-philic carbon material core in step (1), 1.6 g of copper-plated multi-walled carbon nanotubes (copper mass fraction 60%, Beijing Dekedaojin Technology Co., Ltd.) and 2000 mL of N-methylpyrrolidone were stirred and mixed uniformly, and then spray granulated to obtain a core-shell structured porous carbon skeleton with an average particle size of 5 μm;

[0063] (3) Vapor-depositing metallic lithium into the carbon skeleton in step (2) so that the metallic lithium is present at any position on the inner surface, pores or outer surface of the carbon skeleton to obtain the lithium-carbon composite material.

[0064] According to weight test, the content of metallic lithium in the lithium-carbon composite material is 50wt%, the inner core of the porous carbon skeleton is silver-containing acetylene black, and the outer shell is copper-plated multi-walled carbon nanotubes.

[0065] Example 2

[0066] This embodiment provides a lithium-carbon composite material, and the preparation method of the lithium-carbon composite material comprises the following steps:

[0067] (1) 53 g of tin tetrachloride, 48.83 g of Ketjen black (Nouryon, EC-300J, average particle size 50 nm) and 5000 mL of n-hexane were mixed evenly, and then a 3 mol / L methylamine solution of metallic lithium was added, stirred until the reaction was complete, and then spray-dried to obtain a granular lithium-philic carbon material core;

[0068] (2) the granular lithium-philic carbon material core in step (1), 5.97 g of nickel-plated single-walled carbon nanotubes (nickel mass fraction of 40%, Beijing Dekedaojin Technology Co., Ltd.) and a mixture of 2 L of ethanol and n-hexane were ultrasonically mixed and then spray granulated to obtain a porous carbon skeleton with a core-shell structure with an average particle size of 50 μm;

[0069] (3) Immersing the carbon skeleton in step (2) in a liquid ammonia solution of metallic lithium at a concentration of 10 mol / L, removing the liquid ammonia, and repeating the operation of step (3) 5 times, so that the metallic lithium is present at any position on the inner surface, pores or outer surface of the carbon skeleton, thereby obtaining the lithium-carbon composite material.

[0070] According to the weight test, the content of metallic lithium in the lithium-carbon composite material is 70wt%, the core of the porous carbon skeleton is tin-containing Ketjen black, and the shell is nickel-plated single-walled carbon nanotubes. The SEM characterization of the lithium-carbon composite material is as follows: Figure 2 As shown in the figure, it can be clearly seen that metallic lithium is filled in any position of the inner surface, pores and outer surface of the carbon skeleton.

[0071] Example 3

[0072] This embodiment provides a lithium-carbon composite material, and the preparation method of the lithium-carbon composite material comprises the following steps:

[0073] (1) In argon, 24 g of magnesium chloride, 30.25 g of conductive graphite KS-6 (special high density, average particle size 6.5 μm) and 1 L of tetrahydrofuran were mixed evenly, and then a 5 mol / L metallic lithium ethylenediamine solution was added, and ultrasonic reaction was completed, and then spray granulation was performed to obtain a granular lithium-philic carbon material core;

[0074] (2) The granular lithium-philic carbon material core in step (1), 5.86 g of titanium-coated graphene (Beijing Dekedaojin Technology Co., Ltd., with a titanium mass fraction of 20%) and 2 L of a mixture of ethylene glycol and p-xylene were ball-milled and mixed uniformly, and then spray-granulated to obtain a porous carbon skeleton with a core-shell structure with an average particle size of 100 μm;

[0075] (3) Mixing molten metallic lithium with the carbon skeleton in step (2) so that the metallic lithium is present at any position on the inner surface, pores or outer surface of the carbon skeleton to obtain the lithium-carbon composite material.

[0076] According to weight test, the content of metallic lithium in the lithium-carbon composite material is 90wt%, the inner core of the porous carbon skeleton is conductive graphite containing magnesium deposition sites, and the outer shell is titanium-plated graphene.

[0077] Example 4

[0078] Compared with Example 2, the mass of Ketjen black in step (1) was replaced with 1.22 g, and the other conditions remained unchanged.

[0079] Example 5

[0080] Compared with Example 2, the mass of Ketjen black in step (1) was replaced with 268.55 g, and the other conditions remained unchanged.

[0081] Example 6

[0082] Compared with Example 2, the mass of nickel-plated single-walled carbon nanotubes in step (2) was replaced with 59.7 g, and the other conditions remained unchanged.

[0083] Example 7

[0084] Compared with Example 2, the mass of the nickel-plated single-walled carbon nanotubes in step (2) was replaced with 1.99 g, and the other conditions remained unchanged.

[0085] Comparative Example 1

[0086] Compared with Example 2, the only difference is that the material provided in this comparative example is pure metallic lithium powder.

[0087] Comparative Example 2

[0088] Compared with Example 2, the only difference is that the lithium-carbon composite material provided in this comparative example is prepared by the method disclosed in Example 5 of CN 105374991A. According to the weight test, the content of metallic lithium in the lithium-carbon composite material is 33.5%.

[0089] Comparative Example 3

[0090] Compared with Example 2, the only difference is that the lithium-carbon composite material provided in this comparative example is prepared by the method disclosed in Example 2 of CN 109309201A. According to the weight test, the content of metallic lithium in the lithium-carbon composite material is 39.8%.

[0091] Comparative Example 4

[0092] Compared with Example 2, the only difference is that in the composite material provided in this comparative example, the core of the core-shell carbon skeleton does not contain a lithium-philic material, and tin tetrachloride is not added in step (1) of the preparation method. According to the weight test, the content of metallic lithium in the composite material is 34.1%.

[0093] Comparative Example 5

[0094] Compared with Example 2, the only difference is that in the composite material provided in this comparative example, the outer shell of the core-shell structure carbon skeleton does not contain a lithium-phobic layer, and step (2) of the preparation method uses pure single-walled carbon nanotubes. After weight testing, the metallic lithium content in the composite material is 64.7%.

[0095] Comparative Example 6

[0096] Compared with Example 2, the only difference is that in the composite material provided in this comparative example, the porous carbon skeleton is not a core-shell structure, but a mixture of granular lithium-philic carbon material and lithium-phobic carbon material randomly distributed, and step (2) of the preparation method does not use spray granulation, but uses suction filtration and drying at 70° C. According to the weight test, the metal lithium content in the composite material is 38.3%.

[0097] Comparative Example 7

[0098] Compared with Example 2, the only difference is that in the composite material provided in this comparative example, the porous carbon skeleton is not provided with a lithium-philic-lithium-phobic core-shell structure, in the preparation method, step (1) does not add tin tetrachloride, and step (2) uses pure single-walled carbon nanotubes. According to the weight test, the content of metallic lithium in the composite material is 35.2%.

[0099] Material performance testing:

[0100] The materials provided in Examples 1-7 and Comparative Examples 1-7 were mechanically rolled into pole pieces, and the pole pieces were assembled into button cells and symmetrical cells for lithium sheets, respectively. The electrolyte was 1 mol / L LiPF6, and the solvent was EC (ethylene carbonate): DMC (dimethyl carbonate): EMC (ethyl methyl carbonate).

[0101] =1:1:1 (vol / vol / vol), add 10wt% FEC (fluoroethylene carbonate) and 2wt% VC (vinylene carbonate).

[0102] The capacity of the lithium metal button cell was tested at 2 mA and 1 V; the capacity of the symmetrical cell was tested at 1 mA / cm 2 and 0.5mAh / cm 2 The cycle test was carried out under the following conditions. If a short circuit or a voltage exceeding ±1V occurred during the cycle, the cycle was considered to be over. The test results are shown in Table 1.

[0103] Table 1

[0104]

[0105]

[0106] From Table 1, we can see the following points:

[0107] (1) By comparing Example 2 with Examples 4-5, it can be seen that the composite material of Example 2 takes into account both cycle performance and specific capacity, which is better than that of Examples 4-5. This is because the molar ratio of the lithium-philic material tin and the granular carbon material in Examples 4-5 is not within the preferred range of the present invention;

[0108] (2) By comparing Example 2 with Example 6-7, it can be seen that the cycle performance and specific capacity of the composite material of Example 6-7 are worse than those of Example 2. This is because the ratio of the lithium-philic material in the inner core and the lithium-phobic layer in the outer shell of the core-shell porous carbon skeleton of Example 6-7 is not within the preferred range of the present invention;

[0109] (3) By comparing Example 2 with Comparative Example 1, it can be seen that the cycle performance of the metal lithium composite material in Comparative Example 1 is poor (test curve as shown in FIG. Figure 3 This is because there is no core-shell porous carbon skeleton in Comparative Example 1, and the metal lithium deposition is uneven during the cycle, resulting in lithium dendrites causing short circuits (such as Figure 3 As shown in the enlarged view of the test curve of Comparative Example 1 in FIG.

[0110] (4) By comparing Example 2 with Comparative Examples 2-3, it can be seen that the cycle performance and specific capacity of the lithium-carbon composite material in Comparative Examples 2-3 are poor (test curves such as Figure 4-5 As shown), this is because although there are carbon nanotube microspheres as the skeleton in Comparative Example 2, the affinity between metal lithium and carbon nanotube microspheres is poor; although there is tin on the porous carbon skeleton in Comparative Example 3, the tin is distributed throughout the porous carbon skeleton, and metal lithium will preferentially deposit on the outer surface of the porous carbon skeleton and is difficult to enter the pores of the carbon skeleton; while in Example 2, a core-shell porous carbon skeleton is used to construct a lithium-philic-lithium-phobic structure from the inside to the outside, and the electric field and ion field are regulated at the same time to regulate the uniform deposition of metal lithium, and the composite material takes into account both cycle stability and specific capacity;

[0111] (5) By comparing Example 2 with Comparative Examples 4-7, it can be seen that the cycle performance of Comparative Examples 4-7 is worse than that of Example 2. The test curves are as follows: Figure 6-7 As shown, this is because the carbon skeletons in Comparative Examples 4-7 do not adopt the core-shell structure porous carbon skeleton in Example 2 that is simultaneously provided with a lithium-philic core and a lithium-phobic shell.

[0112] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A porous carbon skeleton material, characterized in that: The porous carbon skeleton material is a granular material having a core-shell structure consisting of a core and a porous shell. Wherein, the inner core is formed by one or more lithium-philic carbon material particles, and the lithium-philic carbon material particles include a granular carbon material and a lithium-philic material deposited on the surface of the granular carbon material; The porous shell is arranged on the surface of the inner core and is formed by interweaving lithium-phobic carbon materials; the shape of the lithium-phobic carbon materials includes any one of linear, tubular or sheet shapes or a combination of at least two of them.

2. The porous carbon skeleton material according to claim 1, characterized in that: The granular carbon material has an average particle size of 10 nm to 50 μm, and preferably includes any one or a combination of at least two of Ketjen black, conductive graphite, acetylene black, Super P, LITX, natural graphite, artificial graphite, fluorinated graphite or activated carbon, preferably any one or a combination of at least two of Ketjen black, acetylene black, Super P or fluorinated graphite; The lithium-philic material includes any one or a combination of at least two of silver, gold, tin, silicon, boron, gallium, aluminum, indium, magnesium or antimony; Preferably, the molar ratio of the lithium-philic material to the particulate carbon material in the particulate lithium-philic carbon material is 1:(0.5-100), preferably 1:(10-50); Preferably, the average pore size of the inner core is 1-10 nm.

3. The porous carbon skeleton material according to claim 1 or 2, characterized in that: The lithium-phobic carbon material comprises a micro-nano carbon material and a lithium-phobic layer located on the surface of the micro-nano carbon material. The micro-nano carbon material includes any one of single-walled carbon nanotubes, multi-walled carbon nanotubes, double-walled carbon nanotubes, carbon nanofibers or graphene, or a combination of at least two thereof; The lithium-phobic layer includes a lithium-phobic element, and the lithium-phobic element is any one of copper, nickel, iron, chromium, manganese, cobalt, vanadium or titanium, or a combination of at least two thereof; Preferably, the mass ratio of the micro-nano carbon material to the lithium-phobic layer in the lithium-phobic carbon material satisfies: based on the mass of the lithium-phobic carbon material being 100%, the mass fraction of the lithium-phobic layer is less than 60%, preferably 30-50%; Preferably, the average pore size of the porous shell is 20-100 nm.

4. The porous carbon skeleton material according to any one of claims 1 to 3, characterized in that: The molar ratio of the lithium-philic material in the core to the lithium-phobic element in the lithium-phobic layer is (1-10):1, preferably (1.5-5):1; Preferably, the average particle size of the porous carbon skeleton material is 1-100 μm, preferably 5-50 μm; Preferably, the mass ratio of the inner core to the outer shell of the porous carbon skeleton material is (1-100):1, preferably (10-50):

1.

5. A lithium-carbon composite material, characterized in that: The lithium-carbon composite material comprises a porous carbon skeleton material according to any one of claims 1 to 4 and metallic lithium filled in the pores of the porous carbon skeleton material and / or distributed on the inner and outer surfaces of the porous carbon skeleton material, wherein the mass fraction of the metallic lithium is greater than 50%, preferably 60-90%, based on the total mass of the lithium-carbon composite material as 100%.

6. A method for preparing the lithium-carbon composite material according to claim 5, characterized in that: The method comprises the following steps: (1) mixing a granular carbon material, a lithium-philic element halide and an organic solvent to obtain a mixed system, adding a low-concentration metallic lithium solution to the mixed system and reacting the system under shaking or stirring to obtain a granular lithium-philic carbon material core; The organic solvent includes any one or a combination of at least two of acetonitrile, N-methylpyrrolidone, liquid ether, liquid ester, liquid alkane or liquid aromatic hydrocarbon; The metallic lithium solution comprises a liquid ammonia solution of metallic lithium and / or an organic amine solution of metallic lithium, and the concentration is lower than 5 mol / L; (2) mixing the granular lithium-philic carbon material core, the lithium-phobic carbon material and the organic solvent in step (1), and spray granulating the mixture to obtain a porous carbon skeleton material with a core-shell structure; (3) immersing the porous carbon skeleton material in step (2) in a high concentration of metallic lithium solution, and then drying, or using evaporation and / or molten lithium infusion methods to allow metallic lithium to exist in the pores and / or on the inner and outer surfaces of the porous carbon skeleton material, to obtain a lithium-carbon composite material; The metallic lithium solution includes a liquid ammonia solution of metallic lithium and / or an organic amine solution of metallic lithium, and the concentration thereof is higher than 6 mol / L.

7. The method according to claim 6, characterized in that The molar ratio of the metallic lithium in the metallic lithium solution to the lithiophilic element in the lithiophilic element halide in step (1) is (1-5):1; Preferably, the organic solvent in step (1) comprises any one or a combination of at least two of n-pentane, n-hexane, cyclohexane, N-methylpyrrolidone, benzene, p-xylene, carbon tetrachloride, tetrahydrofuran, liquid paraffin or 1,2-dichloroethane, preferably any one or a combination of at least two of N-methylpyrrolidone, p-xylene, tetrahydrofuran or benzene; Preferably, the concentration of the metallic lithium solution in step (1) is (0.1-4) mol / L, preferably (2-3.5) mol / L.

8. The method according to claim 6 or 7, characterized in that: The organic solvent in step (2) includes any one of N-methylpyrrolidone, ethanol, ethylene glycol, acetone, tetrahydrofuran, n-hexane, p-xylene, heptane or ethylene glycol dimethyl ether, or a combination of at least two thereof.

9. A metal lithium composite negative electrode, characterized in that: The lithium battery comprises the lithium-carbon composite material as claimed in claim 5.

10. A lithium battery, characterized in that: The lithium battery comprises the metal lithium composite negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Metal lithium-framework carbon composite material and preparation method thereof, negative electrode and secondary battery

    CN105374991A

  • Porous carbon framework-nanoparticle composite material, metal lithium complex thereof, as well as preparation methods and application thereof

    CN109309201A